Who's Cashing In? Contemporary Perspectives on New Monies and Global Cashlessness - Sen, Atreyee (Critical Interventions: A Forum for Social Analysis, 2020)
Cashless infrastructures are rapidly increasing, as credit cards, cryptocurrencies, online and mobile money, remittances, demonetization, and digitalization process replace coins and currencies around the world. Who's Cashing In? explores how different modes of cashlessness impact, transform and challenge the everyday lives and livelihoods of local communities. Drawing from a wide range of ethnographic studies, this volume offers a concise look at how social actors and intermediaries respond to this change in the materiality of money throughout multiple regional contexts.